Variation and stability of Polish Retraction in Optimality Theory - Dunin-Borkowski, Jakub (Papers in Linguistics, 2026)
In classic Optimality Theory (OT), constraints are ranked categorically. Such an approach predicts that outputs of a given grammar do not exhibit phonological variation. Variation is, however, present in natural languages. In order to address this issue in OT, it has been proposed that categorical ranking should be abandoned in favor of probabilistic ranking. Probabilistic ranking, however, encounters problems when a process applies variably to some forms, but categorically to other forms. In such cases, lexically indexed constraints are invoked in order to account for the observed exceptionality. While lexical indexing is a successful formal device, it does not predict the behavior of novel forms. This paper reanalyzes the process of Retraction found in Polish. Retraction applies categorically across morphological boundaries, but it may apply categorically or variably inside morphemes. A solution to this issue is found in the interaction of phonology with morphology and the lexicon. In this view, abstract Underlying Representations coexist with listed words. The proposed model employs probabilistic constraint ranking and whole-word storage, retaining the formal convention of lexical and morphological indexing. The model is compatible with the framework of Derivational OT, which is necessary to account for the opaque interaction of Retraction and palatalization.